Philosophy of mind - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Film For The Humanities & Sciences, 2004)
This program seeks to understand the mind/matter dichotomy through the eyes of some of history's keenest philosophers, including Descartes, Wittgenstein, Leibniz, Mill, Gilbert Ryle, Willard Van Orman Quine, Thomas Nagel, and John Searle. Three of today's leading lights in this intriguing branch of philosophy Colin McGinn and Brian McLaughlin, both of Rutgers University, and NYU's Ned Block share their views as well. Descartes's Meditations, Wittgenstein's Philosophical Investigations, and Quine's 2Mind and Verbal Dispositions3 are consulted
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD format
Keywords: Philosophy; Cognitive science; Philosophy of mind; Mind and body